Evaluation of University Websites in Nigeria using the Web Content Accessibility Guidelines - Emeka Ogbuju; Olalekan Ihinkalu; Emmanuel Ajulo; Oluwayemisi Jaiyeoba; Victoria Yemi-Peters (Journal of Computing Theories and Applications, 2023)
Providing accessible open educational resources (OER) is essential for users with impairments to access university resources. To achieve this, web content accessibility guidelines (WCAG) have been developed. In this study, we used the AChecker web accessibility evaluation tool to assess the content of 42 federal university websites in Nigeria and recorded their conformance level to the WCAG. The findings show that at Level A (Minimal Compliance), there were 855 known problems, 55 likely problems, and 7536 potential problems. At Level AA (Acceptable Compliance), 2516 known problems, 58 likely problems, and 15537 potential problems were identified. At Level AAA (Optimal Compliance), 2679 known problems were found, while there were no likely problems, and 16772 potential problems. The results indicated that most websites did not conform to the accessibility guidelines, highlighting the need for educational institutions to comply with WCAG2.1 content standard. The study recommends introducing accessibility training courses in web design and development to ensure effective OER creation for people with diverse abilities. Furthermore, enforcing the implementation of these guidelines by flagging down non-compliant educational websites was suggested. There is a problem of lack of accessibility in federal university websites in Nigeria, leading to unequal access to web content for users with varying abilities. The study aimed to identify aspects of the websites where accessibility needs to be improved and promote diversity and inclusiveness for users with different abilities to have equal access to web content.